PENGELOLAAN PERTUMBUHAN DAUN UBIKAYU (Manihot esculenta Cranzt) MELALUI MULSA JENIS KULTIVAR DAN INTEVAL PEMOTONGAN TUNAS - Hadi Rianto; Historiawati Historiawati; Siti Nurul Iftitah (JURNAL VIGOR, 2020)
This research entitled Maintaining Growth of Cassava Leaves (Manihot esculenta Cranzt) through Mulching, Types of Cultivars, and Buds Cutting Intervals. The experiment was carried out in Balesari Village, Windusari District, Magelang Regency within six months. The aim is to study the growth patterns of cassava leaf shoots and to collect factual practice about the cultivation of cassava leaf which was not yet widely available. A faktorial experiment (2x2x3) which was repeated three times in a completely randomized design. This experiment tested the use of black silver plastic mulch, two cassava Rengganis cultivars, and Indung, with three levels of bud cutting intervals 45, 50 and 55 days after planting. Each treatment was repplicated three times. The results of this experiment indicate that the growth of shoots, namely the weight and length of buds formed is strongly influenced by the type of mulch, cultivar and shoot cutting intervals. Shoot shoots that grow with plastic mulch are better and shoot cutting intervals can also improve shoot shoots. While shoot lengths that grow on Rengganis cultivars are longer than Indung cultivars, there are interactions betweenplastic mulch, cultivars and cutting intervals